Armyworm, Pseudaletia unipuncta (Haworth) (Insecta: Lepidoptera: Noctuidae) - John L. Capinera (EDIS)
EENY-394, a 5-page illustrated fact sheet by John L. Capinera, describes this "true armyworm", a light reddish brown nocturnal moth bundant in North America east of the Rocky Mountains, whose larvae are notorious for appearing out of nowhere to inflict a high level of defoliation in grain crops.  Includes selected references.  Published by the UF Department of Entomology and Nematology, October 2006.